Influence of the Tower Mill’s Classifying Column Structure on the Size of Collected Products - Takashi Furuyama; Sukeyuki Mori; Norio Hashiguchi; Takafumi Okuma (International Mineral Processing Congress, 2003)
"In order to achieve a high recovery of particles finer than 10µm, three types of dry Tower Mill (VD-1, KD-1, KD-2 and KD-3) have been developed. These mills differ from each other in the size of the comminuting part, the inside diameter and shape of the classifying part and the system involved in the collecting process. The last version (KD-3) of tower mills in which the comminuting and classifying operations has been separated, can produce particles finer than 10µm from a limestone ore sizing from 420 to 3360µm. In this tower mill, products in comminuting section are blown up and transported into the classifying column, made of an inverted cone on top of a cylinder, before they agglomerate and settle down. Fine particles are deported and recovered in a cyclone with a central spiral ribbon.Previous studies on the grinding efficiency of the tower mill KD-3 have shown how the maximum size of collected products increased with the airflow velocity, disturbing in the same way a smooth regulation of the grinding operation with the tower mill KD-3. A complete knowledge of factors that influence the maximum size of collected products is needed, therefore, to increase the efficiency of the grindingclassifying operation and ensure a better control over the collected products. The present study deals with this issue and, assuming that the structure of the classifying column could be one of these factors, its internal structure was modified (insertion of vertical plates, cone or horizontal nets) before carrying out comminution tests that would establish a relationship between the inward shape of the column and the maximum size of collected products. It was found that the weight of products collected in the cyclone decreases when a cone or some horizontal nets are inserted inside the column. At the same time, the weight of products collected in the column increases. This is due to the fact that coarse particles blown up from the comminution section collide with the base of the cone or the nets and settle down the bottom of the classifying column. Therefore, the cone and some horizontal nets inserted inside a classifying column, have the particularity to stabilize the maximum size of particles (15.1-17.5µm and 8.4-11.3µm) in the cyclone even when the airflow velocity in duct increased. These tools could of great help in the production of particles of definite size to fit for instance the paper industries requirements (production of limestone material sizing - 10µm as paper filler)."